Developing a complexity leadership competency framework for the Governance and Administration Cluster of the South African Public Service - Van Dijk, Hilligje Gerritdina (University of Pretoria, 2021)
Thesis (PhD (Public Administration and Management))--University of Pretoria, 2021.